Criteria for the Asymptotic Stability of Solutions of Dynamical Systems - Valeyev, K. G.; Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a new proof for criteria for the asymptotic stability of systems of difference and differential equations based on the properties of monotone operators in a semiordered space. We also establish necessary and sufficient conditions for the asymptotic stability of stochastic systems of differential and difference equations in the mean square.